VIRTUAL SCREENING OF PHYTOCHEMICALS OF MORINDA CITRIFOLIA AS ANTI-INFLAMMATORY AND ANTI-ALZHEIMER AGENTS USING MOLEGRO VIRTUAL DOCKER ON p38-Î± MITOGEN ACTIVATED PROTEIN KINASE ENZYME - Markandeyan, Devaprasad; Santhalingam, Kumaran; Kannaiyan, Subramaniyan; Suresh, Sanmathi; Paul, Benedict (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Pharmacological and genetic inhibition of p38Î± mitogen-activated protein kinase (p38Î± MAPK) has potential in the treatment of human diseases such as autoimmune diseases, heart failure, Alzheimer disease, and Parkinsonism. Our aim is to do in-silico screening of phytochemicals of Morinda citrifolia for p38Î± MAPK inhibitory property by docking method. Methods: We did docking of various phytochemicals present in M. citrifolia against p38Î± MAPK enzyme extracted from Protein Data Bank (ID-4F9Y), by utilizing the Molegro virtual docker Software. The docking scores of phytochemicals were compared with the scores of native reference ligands present in the crystal structure 4F9Y. Results: Isoprincepin and balanophonin show better docking scores when compared to reference ligands in the protein. Isoprincepin has potential to act in a highly selective manner on p38Î± MAPK as it binds to Met 109 in the phylogenetically conserved kinase hinge region and thereby induces a conformational change known as glycine flip phenomenon. Balanophonin has favorable physiochemical properties for blood-brain barrier penetration and can act on p38Î± MAPK in the brain. Conclusion: Some of the phytochemicals present in M. citrifolia have p38Î± MAPK binding and possible inhibitory potential. Keywords: p38Î± mitogen-activated protein kinase, Isoprincepin, Balanophonin, Molegro virtual docker.